Edukacja wielokulturowa szansą na integrowanie uchodźców ze społecznością lokalną - Nazaruk , Stanisława; Klim-Klimaszewska, Anna (Studia Edukacyjne, 2017)
Currently we are witnessing migration, which for different reasons exhibits a growth tendency. It does not just concern big cities, but also smaller towns, where we can encounter people with different cultural backgrounds, religion, dialect, and values. Multicultural education comes out to meet the expectations of the minorities and its main purpose is to create a platform for dialog and communication, as well as the composition of educational programs and multicultural upbringing. The article explains the situation of refugees, with emphasis on the education and upbringing of children. It provided examples of multicultural education implemented in a small elementary school from a County of Bielsk.